Strategi Pembelajaran Studi Hadis bagi Generasi Remaja - Anadila Afifah; Qoidatul Marhumah; Zuhri Humaidi; Moh. Misbakhul Khoir (Gunung Djati Conference Series, 2023)
This study aims to discuss learning strategies for the study of hadith for the youth generation. This study uses a qualitative approach by applying a descriptive-analytical method. The results of the study state that it is important to shape change, innovation, and strategies to prepare oneself as an educator who understands the backgrounds and abilities of each student or youth. According to Muzakkir's view, the learning strategy for the study of hadith for youth emphasizes innovative efforts and is in line with the times. This becomes half in the success of the learning achievement process. Educators must be actively involved in the learning process, one of which is being able to apply strategies that are both innovative and fun so that students can understand learning and their psychological aspects also develop well.